Model Enterprise Architecture for Information Technology Services in Universities - Batmetan, Johan Reimon (JR Education, 2022)
Enterprise Architecture Documents are very important in the development of Information Technology systems in an institution. The Enterprise Architecture contains a strategic plan for the development of ICT and the services that will be run by the system. The preparation of the IS/IT strategic plan at Universitas Negeri Manado is a step in aligning information systems and technology in accordance with the Universitas Negeri Manado business processes and strategies. The method used in this research is descriptive qualitative research using primary and secondary data and building an information technology enterprise architecture using the TOGAF framework model. Collecting data with interviews, documentation, questionnaires, and direct observation of the organization. The analysis used is the Value Chain, SWOT, PEST, Porter's Five Force, and Critical Success Factor (CSF) methods. The results of this study are the form or formulation of the Enterprise Architecture strategic plan of IS/IT in accordance with the Universitas Negeri Manado, in the form of data architecture, applications, and technology to support the business processes of Universitas Negeri Manado.